EdQuizy: A Development of a Quiz Mobile Application with Anti-Cheating Features - Wan Osman, Wan Nurfasihah Najwa; Ab Rahman, Ts Dr. Nurul Hidayah (Applied Information Technology And Computer Science, 2023)
Quiz is a simple test that is used to observe and evaluate the performance of individuals. Recently, Covid-19 has spread and impacted education system. Class assessments such as quiz and final exams are run using an online platform. Teacher used an existing online quiz application that was provided online to conduct the quiz but limited quiz application that focuses on security and anti-cheating. Therefore, online quiz mobile application with anti-cheating features, EdQuizy is created. EdQuizy application is available in Android Studio using Java language. The application is developed to minimize students cheating during quiz by implementing anti-screenshot and randomized quiz answer option order in student module. FLAG_SECURE is used to implement the anti-screenshot to prevent the window’s content from being viewed on non-secure displays. While, fisher-Yates shuffle algorithm is applied to randomized the quiz answer option order. EdQuizy provide three users which include teacher, admin and student. The application required teacher to manage quiz and class and student took the quiz. Evolutionary prototyping model is used as a methodology. As a result, EdQuizy can reduce student dishonesty during the quiz with the anti-cheating features that implemented in the application.